Imaging the Atomic Surface Structures of CeO2 Nanoparticles - Lin, Yuyuan; Wu, Zili; Wen, Jianguo; Poeppelmeier, Kenneth R; Marks, Laurence D (Nano letters, 2014)
Atomic surface structures of CeO2 nanoparticles are under debate owing to the lack of clear experimental determination of the oxygen atom positions. In this study, with oxygen atoms clearly observed using aberration-corrected high-resolution electron microscopy, we determined the atomic structures of the (100), (110), and (111) surfaces of CeO2 nanocubes. The predominantly exposed (100) surface has a mixture of Ce, O, and reduced CeO terminations, underscoring the complex structures of this polar surface that previously was often oversimplified. The (110) surface shows “sawtooth-like” (111) nanofacets and flat CeO2–x terminations with oxygen vacancies. The (111) surface has an O termination. These findings can be extended to the surfaces of differently shaped CeO2 nanoparticles and provide insight about face-selective catalysis.